Segmental Box Girder (SBG) Monitoring and Control System in Light Rail Transit Line 3 (LRT3) Construction Project using Microsoft Project - Nur Atiqah Iryani Binti Ismail; Mohd Eizzuddin Bin Mahyeddin (Progress in Engineering Application and Technology, 2022)
Malaysia is a developing country with numerous new construction and buildings scattered across the country. However, not all construction projects are successful and run smoothly, in some cases, a project may be problematic and fail. Failure to complete the project on schedule will be caused delays in the future. One of the ongoing railway construction projects in Malaysia is the construction and completion of the Light Rail Transit Line 3 (LRT3) from Bandar Utama to Johan Setia. A study was conducted at AlKauthar Kinematics Sdn Bhd company which is involved in the construction of the LRT3 project and focuses on the casting and installation of Segmental Box Girder (SBG). In order to improve the delivery of successful projects, the aim of this study is to determine the factors of construction project delay, analyze the affected cost and time in construction project using Microsoft Project and propose ways to minimize the construction project delay. Method used in this study is analyzing the data obtained from industry using Microsoft Project. From the findings, it can be concluded that the factors of the delay in LRT3 construction project at GS10 package are MCO period cause by covid-19, conditions on construction site, delivery of material and defects on some segments. This will help all government and private construction organizations in overcoming project failure.